Workshop Penggunaan Software Kecerdasan Buatan untuk Mempercepat Proses Penulisan Karya Ilmiah yang Berkualitas bagi Akademisi - Pudjiarti, Emiliana Sri; Ratnawati Dwi P, Honorata (Perigel: Jurnal Penyuluhan Masyarakat Indonesia, 2023)
Advances in artificial intelligence technology are increasingly being used to accelerate and improve the quality of various fields of work, including academic research. Referring to this, online training on the use of AI software for 287 lecturers from universities throughout Indonesia has been interactive. This 3-day training provides practical learning regarding the features and benefits of software such as Claude, GPT-3, and Elicit as well as Publish or Perish for literature review assistance; quantitative and qualitative data analysis; writing drafts of scientific articles; to editing published works. Post-training evaluation shows a significant increase in lecturers' digital literacy in utilizing artificial intelligence to accelerate the research cycle and publication of reputable journals. The enthusiasm of the participants shows the urgency of expanding similar programs so that lecturer competence is more competitive in the industrial era 4.0 to increase the productivity and quality of research and scientific work in higher education institutions in Indonesia.